Mitral valve replacement with the preservation of the entire valve apparatus - Alsaddique,Ahmed A. (2007)
OBJECTIVE: The papillary muscles and the chordae tendineae of both mitral leaflets contribute to the preservation of the left ventricular function. Most surgeons, however, routinely excise the anterior mitral leaflet. METHODS: In a group of nine patients, six of them underwent mitral valve replacement alone and three underwent both aortic and mitral valve replacements, all the mitral apparatus was preserved. All of these patients had mechanical valves using CarboMedics cardiac prosthesis (CarboMedics, Inc. Austin, Texas). RESULTS: There was no mortality. Postoperative echocardiographic assessment revealed maintained left ventricular function with no interference with the prosthetic leaflet mobility and no left ventricular outflow tract gradient. CONCLUSION: We believe that in most patients with long-standing mitral valve regurgitation, thinned out papillary muscles and elongated chordae tendineae that are not amenable to repair, valve replacement with the preservation of the entire native valve is possible and should be encouraged. This is especially valuable for those with depressed left ventricular function, who might otherwise suffer from left ventricular dysfunction in the long-term if the entire mitral valve apparatus were to be excised.